Persepsi Siswa Terhadap Kegiatan Ekstrakurikuler Pramuka pada Sekolah Menengah Kejuruan (SMK) di Kecamatan Padang Timur - Anggia Tamara; Ahmad Sabandi; Hanif Al Kadri; Yulianto Santoso (Journal of Educational Administration and Leadership, 2021)
This research aims to get information about students’ perception of scout extracurricular activities in vocational schools in east Padang subdistrict as seen from indicators of interest, attitude, motivation, attention, appreciation and expectations. The type of research used is desscriptive research using quantitative methods. In this research, the population of students at SMK in East Padang subdistrict which amounted to 325 students, the large sample taken was 76 respondents. The withdrawal of samples in this research using Proportional Stratified Random Sampling. Data collection using questionnaires with likert scale has been tested for validity and reliability. The average formulation is used in processing data in this research. The data showed the response of students regarding scout extracurricular activities at vocational schools in east Padang regarding scout extracurrilar activities at vocational schools in east padang subdistrict from: (1) the interest aspect is getting an average score of 2.53 with a respondent achievement rate (TCR) of 58.8% in the low category; (2) aspect of attitude are getting an average score of 2.65 and the respondent’s achievement rate (TCR) of 61.8% in the low category; (3) the motivational aspect is to get an average score of 2.61 and the respondent’s achievement rate (TCR) of 57.2% in the low category; (4) the attention aspect is to get an average score 2.59 and the respondent’s achievement rate (TCR) of 60.6% in the low category; (5) the aspect of appreciation is to get an average score of 2.47 with a respondents’s achievement rate (TCR) of 57.7% in the low category; (6) the aspect of expectation is to get an average score of 2.41% and the respondent’s achievement rate (TCR) of 57.0% in the low category. Overall, student’s perception of scout extracuricular activities in vocational schools in east Padang subdistrict scored an average of 2.54 with a respondent’s achievement rate (TCR) of 58.85% in the low category.